Addressing Health Disparities Among Families: Policy Approaches to Improve Infant Health - Summer Sherburne Hawkins (Journal of Moral Theology, 2021)
The author discusses the results of her evidence-based research showing that fiscal policies, particularly taxes, have downstream effects on infant health by influencing parental health behaviors as well as women’s health habits during pregnancy. As a case study, across U.S. state cigarette tax increases led to the largest benefits for the most vulnerable mothers and infants by proving that tobacco control policies, particularly cigarette taxes, reduce prenatal smoking and improve birth outcomes among the most vulnerable infants. Hence, an evidence-based approach to population health could promote needed policies aimed at improving the health and well-being of the most vulnerable children and families.